2013
DOI: 10.1002/cphc.201300620
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Debris on Graphene Oxide Films

Abstract: We study the effect of oxidative impurities on the properties of graphene oxide and on the graphene oxide Langmuir-Blodgett films (LB). The starting material was grupo Antolín nanofibers (GANF) and the oxidation process was a modified Hummers method to obtain highly oxidized graphene oxide. The purification procedure reported in this work eliminated oxidative impurities decreasing the thickness of the nanoplatelets. The purified material thus obtained presents an oxidation degree similar to that achieved by ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
88
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(100 citation statements)
references
References 70 publications
11
88
1
Order By: Relevance
“…However, the oxidation peaks are considerably smaller compared to those of aGO which indicates that the quantity of oxygen moieties in aGO decreases after the removal of OD. In comparison, a similar reduction of degree of oxidative functionality was reported for bwGO [7,48,49]. Rourke et al, found that O/C ratio reduced from 0.5 in aGO to 0.25 in bwGO [7].…”
Section: Characterization Of Ago and Acgosupporting
confidence: 69%
“…However, the oxidation peaks are considerably smaller compared to those of aGO which indicates that the quantity of oxygen moieties in aGO decreases after the removal of OD. In comparison, a similar reduction of degree of oxidative functionality was reported for bwGO [7,48,49]. Rourke et al, found that O/C ratio reduced from 0.5 in aGO to 0.25 in bwGO [7].…”
Section: Characterization Of Ago and Acgosupporting
confidence: 69%
“…It should be noted that this separation technique most likely did not remove "oxidation debris" from GO flakes [54,55] as can be deduced from UV-VIS spectra (data not shown). The adsorption peak at 234 nm detected in both samples, in good agreement with peak maximum for GO [55,56], suggests no substantial change in chemical composition of GO-S2 compared to GO. The biocathode GCE||Er(GO-S2 + BOD "in-situ") provided 2.7-fold higher current j = (120 ± 19) μA cm − 2 compared to the biocathode based on as-received GO flakes (Fig.…”
Section: Resultssupporting
confidence: 80%
“…However, since solid coverage and sheet wrinkles can be influenced by nanoplatelet size 31 and electric charge, 53 ζ potential and nanoplatelet size were previously determined. In a previous work, 14 ζ potential values of NGO and PNGO aqueous solutions were determined and they showed a bimodal distribution for NGO, centered at −34 and −50 mV, and a broad distribution centered at −20 mV for PNGO. In the current work, the ζ potential values obtained for GO and PGO, shown in Figure 1c, present a similar trend: a bimodal distribution centered at −42 and −65 mV for the nonpurified sample, GO, and a broad distribution centered at −34 mV for PGO, although the electric charge of graphene oxide synthesized from graphite is higher than that of sheets obtained from GANF.…”
Section: Resultsmentioning
confidence: 99%
“…22,24 These fragments are strongly adsorbed on the graphitic sheets through π−π stacking interactions 8,25 and can be removed by alkaline washing of GO. The purified material contains a lower amount of Ogroups than nonpurified ones 14,22,24,26 and presents a similar oxidation degree to that achieved by chemical reduction of GO. 14 According to this information, the structure of purified graphene oxide is quite different from the nonpurified one.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation